Evaluation of the lateral acceleration on highway comfort: A case study with university students - Boztas, Abdullah Erdem; Ozen, Halit (YILDIZ TECHNICAL UNIV, 2023)
Highway geometric standards are defined depending on the road users-both passengers and drivers- and vehicle characteristics, as well as the land structure on which the route is located. The limit values for the radius of the horizontal curves, the maximum flow rate, and the combination of the curve characteristics are calculated according to the safety and comfort parameters. As the comfort parameter, lateral acceleration acting on the passenger while traveling on a curved section or the change of this lateral acceleration in unit time is used. In the current situation, the limit value of the lateral acceleration used in Turkey is 1.47 m/s2 [1]. However, it is not known if this value is still suitable considering the technology enhancements and the changes in people's expectations. The limit value of lateral acceleration brings out negative economic consequences for both the users and constructers when it is lower than necessary. Too safe standards force constructers to increase the radii of the curves which increases the construction costs or creates a need for speed limitation which increases the fuel costs via braking and accelerating. This study aims to evaluate the suitability of the existing limit value with a case study involving test drives and a survey. During the test drives different levels of lateral acceleration geometrically permissible within the vehicle are produced and the level of perception of this lateral acceleration is determined. Within the scope of the project, the case study is done with university students. In the survey, participants are asked to answer demographical questions and rate their level of comfort perception. The perception levels are considered in five different categories according to the level of discomfort. Data such as age, vehicle ownership, gender, weight, height, and transportation mode choices for their regular trips were also taken from the participants and the relationship between these and comfort perception was investigated. The results obtained from this study were investigated to determine whether it is necessary to disseminate the study to a broader group and whether the limit value is suitable for the age group we studied with. The results of this study, which will contribute to the literature in terms of evaluating this common standard, showed that the lateral acceleration limit value is lower than necessary and an advanced study with larger groups may suggest changing the standard.
Keywords: Highway Geometric Standards; Lateral Acceleration; Perception Of Comfort; Engineering